Public Health Management of Persons Under Investigation for Ebola Virus Disease in New York City, 2014-2016. (September 2019) - Winters, Ann; Iqbal, Maryam; Benowitz, Isaac; Baumgartner, Jennifer; Vora, Neil M.; Evans, Laura; Link, Nate; Munjal, Iona; Ostrowsky, Belinda; Ackelsberg, Joel; Balter, Sharon; Dentinger, Catherine; et al.
During 2014-2016, the largest outbreak of Ebola virus disease (EVD) in history occurred in West Africa. The New York City Department of Health and Mental Hygiene (DOHMH) worked with health care providers to prepare for persons under investigation (PUIs) for EVD in New York City. From July 1, 2014, through December 29, 2015, we classified as a PUI a person with EVD-compatible signs or symptoms and an epidemiologic risk factor within 21 days before illness onset. Of 112 persons who met PUI criteria, 74 (66%) sought medical care and 49 (44%) were hospitalized. The remaining 38 (34%) were isolated at home with daily contact by DOHMH staff members. Thirty-two (29%) PUIs received a diagnosis of malaria. Of 10 PUIs tested, 1 received a diagnosis of EVD. Home isolation minimized unnecessary hospitalization. This case study highlights the importance of developing competency among clinical and public health staff managing persons suspected to be infected with a high-consequence pathogen.